HUBUNGAN PARITAS DENGAN KEJADIAN PERDARAHAN POSTPARTUM DI RSUD dr.MURJANI SAMPIT TAHUN 2017 - dewi sartika (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2019)
Background: According to WHO (World Health Organization) the main cause of maternal death in Indonesia is 67% bleeding. In Central Kalimantan in 2015 the highest cause of death was bleeding. High parity is one of the risk factors for postpartum bleeding. Objective: To determine the correlations between parity with incident postpartum bleeding at dr. Murjani Hospital Sampit 2017. Research Method: The research method was carried out analytically with a retrospective approach to maternity mothers who experienced postpartum bleeding and who did not experience postpartum bleeding at dr. Murjani Hospital Sampit 2017. Results: From the results of statistical tests using Chi-Square test with ? = 0.05 (5%), obtained p value = 0,000 which means that p <0.05 then H0 is rejected and Ha is accepted so it can be concluded that there is a significant correlations between parity and the incidence of Postpartum Bleeding at dr. Murjani Hospital Sampit 2017. Conclusion: There is a significant corelation which is indicated by the value of ?- value: 0.000 level of 0.05 (5%), so that p <0.05 between the Corelation parity with the incidence Postpartum Bleeding at dr. Murjani Hospital Sampit 2017.